The Effects of Computer-aided Instruction on Learning and Attitudes in Economic Principles Courses: Revised Results. - Henry, Mark (Journal of Economic Education)
This article examines the effects of the Teaching Information Processing System (TIPS), a computer-aided instruction, on the performance of principles-of-economics students on the post-Test of Understanding of College Economics exam. One student had erroneously been reported as being in the TIPS group when in fact he was in the control group. The data error allowed regression coefficients to be computed for three dummy variables: TIPS, section one (D1) and section two (D2). Without the data error, coefficients for TIPS, D1 and D2, cannot be computed since TIPS is equal to the sum of D1 and D2 and inversion of the X'X matrix is not possible.